Tuning of ring-shaped piezoelectric-transformer efficacies by structural and electrode design: Finite element diagnosis - Chumpol Supatutkul (2018)
© 2015 Taylor & Francis Group, LLC. In this work, Finite Element method (FEM) was used to model ring-shaped piezoelectric-transformers, using piezoelectric parameters from PZT-5H and having polarization along thickness direction. The resonator with full-covered electrode on top and bottom areas of the ring was firstly considered to investigate the dimensional effect on available vibrational modes. For modes above the fundamental, the results show that with increasing the ring thickness, the vibrational modes shift to lower frequencies. Similarly, with increasing the width, the resonant frequencies reduce. On the other hand, with increasing the ring-radius while keeping the width fixed, the resonant modes maintain. Eigenmode diagram of these resonant frequencies was also presented as databases for future use. Further, to enhance the power transferring efficiency, the electrode layouts were investigated where input and output electrodes were designed to correspond with electrical distribution of desired vibrational modes. The alternating and non-alternating electrode layouts were considered in this work. With the lumped-equivalent circuit model, the results show significant improvement of the considered resonant modes due to the enhancing of charge accumulation on the electrodes. In addition, the alternating electrode gives electromechanical coupling coefficient higher than that of the non-alternating electrode when operated at the same condition. This therefore implies the alternating electrode layout, corresponding to the electrical distribution of a particular vibrational mode, suggesting itself as a promising choice for implementation to achieve highly efficient piezoelectric-transformer.